Addition Of Various Concentrations Of Gadung Tuber Starch Which Is Determined As A Binder To The Physical Properties Of Mefanamic Acid Tablets By Wet Granulation - Sinaga, Alex Handani; Fendri , Novicha Aulya (SEAN Institute, 2023)
n previous studies, the polysaccharide extract of gadung tuber has a hypoglycemic effect, wherein the plant contains a high glycemic index indicating that carbohydrates undergo rapid digestion and are absorbed in large quantities so that blood glucose levels suddenly experience a rapid rise in insulin which can lower cholesterol values. (Sumunar et al., 2015) This research method is an experiment in which this research was carried out, by making starch from gadung starch and making tablets by wet granulation. Based on the results of the research that has been done, it can be concluded that the use of gadung starch as a binder can produce mefanamic acid tablets that meet the requirements for uniformity of tablet weight, tablet hardness, tablet friability, and tablet disintegration time in the Indonesian Pharmacopoeia. The addition of gadung starch (Discorea Hispida Dennst.) as a binder to mefanamic acid tablets causes differences in the physical properties of the tablets, namely in greater tablet hardness, smaller tablet friability and longer tablet disintegration time. The significance value obtained was 0.00 <0.05, because there was a significant difference in the gadung formulation and the gadung formulation as a binder for mefanamic acid tablets